If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 5(2x + 1) = 35 Reorder the terms: 5(1 + 2x) = 35 (1 * 5 + 2x * 5) = 35 (5 + 10x) = 35 Solving 5 + 10x = 35 Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-5' to each side of the equation. 5 + -5 + 10x = 35 + -5 Combine like terms: 5 + -5 = 0 0 + 10x = 35 + -5 10x = 35 + -5 Combine like terms: 35 + -5 = 30 10x = 30 Divide each side by '10'. x = 3 Simplifying x = 3
| 6-7x=22-21x | | -99-9x=10x+15 | | 28=6+8 | | -3x^2+6x-1=0 | | 17d^2-4d=0 | | P^4-60*P^2-799=0 | | (5x-1)*(2-x)=(x-3)*(2-5x) | | 2x+1=-3x-9 | | 2x+6=20-5x | | (x)2+3x-2=0 | | q-13=8 | | 2*3n+8=1*2n+2 | | -95-7x=9x+17 | | x+18=27 | | 6x+6=-99-9x | | 13w=169 | | 4r-19=19 | | -3x-5=-44 | | -(-4+-12)= | | y-2=y | | (n+1)*8=48 | | A(x+1)+b(x-2)=16 | | 7x^2=42x | | (n-6)*5=45 | | 5(2x-1)=2(x-3) | | 14-(-3)= | | 3x-11=21 | | X+7=29 | | 4(x+3)=x+3 | | a-3r=r(a+1) | | 2(3-4.2)2= | | 9x+6=3x-18 |